The lord of the rings. The two towers - Jackson, Peter, 1961-; Wood, Elijah, 1981-; McKellen, Ian.; Tyler, Liv.; Mortensen, Viggo, 1958-; Astin, Sean.; Blanchett, Cate, 1969-; Rhys-Davies, John.; Boyd, Billy, 1968-; Monaghan, Dominic, 1976-; Bloom, Orlando, 1977-; Serkis, Andy.; et al. (Los Angeles : New Line Home Entertainment, 2003)
The Fellowship has been broken. Boromir is dead; Frodo Baggins and Samwise Gamgee have gone to Mordor alone to destroy the One Ring; Merry and Pippin have been captured by the Uruk-hai; Aragorn, Legolas, and Gimli have made friends of the Rohan, a race of humans that are in the path of the upcoming war, led by its aging king, Theoden. The two towers between Mordor and Isengard, Barad-dur and Orthanc, have united in their lust for destruction. The corrupt wizard Saruman and his slimy assistant, Grima Wormtongue, have created a grand Uruk-hai army bent on the destruction of Man. The rebellion against Sauron is building up, led by the wizard Gandalf the White. One of the Ring's original bearers, the creature Gollum has tracked Frodo and Sam down in search of his "precious", but is captured by the Hobbits and used to lead them to Mt. Doom. The War of the Ring begins.
Based on the book by J.R.R. Tolkien.
Special features: Discs 1 & 2: four separate audio commentary tracks by the director and writers, the design team, the production and post-production team, and the cast.
Special features: Disc 3: six documentaries: J.R.R. : Origins of Middle Earth; From book to script : finding the story; Designing and building Middle Earth; Gollum; Middle Earth atlas; New Zealand as Middle Earth.
Special features: Disc 4: five documentaries: Filming The two towers; Visual effects; Editorial : refining the story; Music and sound; The battle for Helm's Deep is over.
Director of photography, Andrew Lesnie ; editor, Michael Horton ; music, Howard Shore ; costume designers, Ngila Dickson ... [et al.] ; production designer, Grant Major ; visual effects supervisor, Jim Rygiel.
Elijah Wood, Ian McKellen, Liv Tyler, Viggo Mortensen, Sean Astin, Cate Blanchett, John Rhys-Davies, Billy Boyd, Dominic Monaghan, Orlando Bloom, Andy Serkis.
Keywords: Baggins, Frodo -- Drama; Middle Earth (Imaginary place) -- Drama; Baggins, Frodo (Personaje literario) -- Teatro; Feature films; Fantasy films; Action and adventure films; Video recordings for hard of hearing people